Subtract $3x - 4y - 7z$ from the sum of $x - 3y + 2z$ and $-4x + 9y- 11z$.

AcademicMathematicsNCERTClass 8

To do:

We have to subtract $3x - 4y - 7z$ from the sum of $x - 3y + 2z$ and $-4x + 9y- 11z$.

Solution:

Sum of $x - 3y + 2z$ and $-4x + 9y - 11z$ is,

$x - 3y + 2z + (- 4x + 9y - 11z) = x - 3y + 2z - 4x + 9y - 11z$

$= x - 4x - 3y + 9y + 2z - 11z$

$= -3x + 6y - 9z$

Subtracting $3x - 4y - 7z$ from $(-3x + 6y - 9z)$

$(-3x + 6y - 9z)-(3x - 4y - 7z)=-3x + 6y - 9z - 3x + 4y + 7z$

$= -3x - 3x + 6y + 4y -9z +7z$

$= -6x + 10y - 2z$

raja
Updated on 10-Oct-2022 13:19:29

Advertisements